Dynamic modelling for the hot blast stove. (1st January 2017) - Zetterholm, J.; Ji, X.; Sundelin, B.; Martin, P.M.; Wang, C.
Highlights: A dynamic model for the hot blast stove system has been developed. The developed model was validated with experimental measurements. The effect of OxyFuel technique on the performance of hot blast stoves was studied. Increasing the cycle time of a stove system can increase the blast temperature. Abstract: A large amount of energy is required in the production of steel where the preheating of blast in the hot blast stoves for iron-making is one of the most energy-intensive processes. To improve the energy efficiency of the steelmaking it is necessary to investigate how to improve the hot blast stove operation. In this work a mathematic model for evaluating the performance of the hot blast stove was developed using a finite difference approximation for the heat transfer inside the stove during operation. The developed model was calibrated and validated by using the process data from hot blast stove V26 at SSABs plant in Oxelösund, Sweden. The investigation shows a good agreement between the measured and modelled data. As a case study, the developed model was used to simulate the effect of a new concept of OxyFuel technique to hot blast stoves. The investigation shows that, by using this OxyFuel technique, it is possible to maintain the blast temperature while removing the usage of coke oven gas (COG). The saved COG can be used to replace some fossil fuel, such as oil and LPG. Furthermore, the effect of the cycle time on the single stove was studied. As expected, both the hot blast and flue gas temperatures are increased when increasing the cycle time. This shows that it is a good strategy for the hot blast stove to increase the blast temperature if the stove is currently not operated with the maximum allowed flue-gas temperature.